SYSTEM LITERATURE REVIEW OCCUPATIONAL STRESS: AN OVERVIEW ANALYSIS BIBLIOMETRICS - Setiawan, Diding; Sopiah (Transpublika Publisher, 2022)
Work stress is psychological reaction and physiological events when ability work of individuals and requirements work are not the same. The fundamental differences felt between individual competencies and the demands of the work environment are called stressor cases which are the same as what happens under pressure of overly responsible responses, job expectations, working conditions and opportunities for development. The aim of this study is to describe and discuss about occupational stress using PRISMA method with bibliometrics analysis technique. Result of filtering journal with the PRISMA method resulting in 35 journals and written by 111 authors. The result of this study is to the variable that is related with this occupational stress, including mental health, work satisfaction, and work performance. Overall, the research is expected to be the right reference for further research, especially researchers who will examine titles that related to work stress.